Oxidative Stress and Inflammation in COVID-19-Associated Sepsis: The Potential Role of Anti-Oxidant Therapy in Avoiding Disease Progression - Jesús Beltrán-García; Rebeca Osca-Verdegal; Federico V. Pallardó; José Ferreres; María Rodríguez; Sandra Mulet; Fabian Sanchis-Gomar; Nieves Carbonell; José Luis García-Giménez (MDPI AG, 2020)
Since the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) outbreak emerged, countless efforts are being made worldwide to understand the molecular mechanisms underlying the coronavirus disease 2019 (COVID-19) in an attempt to identify the specific clinical characteristics of critically ill COVID-19 patients involved in its pathogenesis and provide therapeutic alternatives to minimize COVID-19 severity. Recently, COVID-19 has been closely related to sepsis, which suggests that most deceases in intensive care units (ICU) may be a direct consequence of SARS-CoV-2 infection-induced sepsis. Understanding oxidative stress and the molecular inflammation mechanisms contributing to COVID-19 progression to severe phenotypes such as sepsis is a current clinical need in the effort to improve therapies in SARS-CoV-2 infected patients. This article aims to review the molecular pathogenesis of SARS-CoV-2 and its relationship with oxidative stress and inflammation, which can contribute to sepsis progression. We also provide an overview of potential antioxidant therapies and active clinical trials that might prevent disease progression or reduce its severity.